Frequency of detection and factors of elevated levels of diabetes-associated autoantibodies in the blood of patients with clinical type 2 diabetes mellitus - Y.A. Saienko; B.M. Mankovsky (Mìžnarodnij Endokrinologìčnij Žurnal, 2025)
Background. Some patients with clinical course of type 2 diabetes mellitus (T2DM) exhibit signs of an autoimmune process, particularly an elevated level of glutamic acid decarboxylase autoantibodies (GADA), indicating an autoimmune component of the disease. Patients with GADA-positive T2DM have a distinct metabolic phenotype, with less pronounced insulin resistance but a more rapid decline in β-cell function, necessitating early insulin therapy. At the same time, data suggest that latent autoimmune diabetes shares certain risk factors with classic T2DM. However, in Ukraine, there are almost no research on the prevalence of GADA among patients with T2DM, limiting opportunities for a personalized approach to diagnosis and treatment. The purpose of the study: to assess the frequency of detecting elevated GADA autoantibodies in patients with a clinical course of T2DM and to determine their association with clinical, metabolic, and social characteristics. Materials and methods. The study included 48 participants with clinically diagnosed T2DM, 30 (62.5 %) men and 18 (37.5 %) women. A comprehensive approach was used to evaluate clinical, biochemical, and anthropometric parameters in patients with T2DM to fully characterize their metabolic profile and phenotype. Results. Patients with GADA-positive T2DM had a significantly later disease onset and a shorter diabetes duration compared to those with classic T2DM, indicating distinct characteristics of each type. They also had significantly lower body mass index and waist circumference, suggesting a lower predisposition to obesity and metabolic disorders compared to participants with classic T2DM. Higher aspartate aminotransferase and alanine aminotransferase levels in classic T2DM patients compared to those with autoimmune diabetes suggest the need for screening for metabolic dysfunction-associated fatty liver disease. Patients with GADA-positive T2DM exhibited significantly lower insulin secretion (as indicated by reduced C-peptide levels). A significantly higher albuminuria level in the GADA-positive group may indicate a greater susceptibility to renal complications. Additionally, patients with autoimmune diabetes rated their health significantly better than those with classic T2DM, which may be related to the slower progression of the disease and fewer cardiometabolic disturbances. Conclusions. Our study demonstrates clear differences in the l course between GADA-negative and GADA-positive T2DM. Determining GADA autoantibody levels in patients with a clinical course of T2DM is crucial for the timely diagnosis of autoimmune diabetes, risk stratification, treatment personalization, and disease prognosis.